2015
DOI: 10.1515/rjim-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Role of signal-averaged electrocardiography and ventricular late potentials in patients with chronic obstructive pulmonary disease

Abstract: Patients with chronic obstructive pulmonary disease (COPD) have an increased risk for cardiac arrhythmias. Ventricular late potentials (VLP) on signal-averaged electrocardiography (SAECG) are associated with an increased risk for malignant ventricular arrhythmias. Our aim is to investigate the modifications of SAECG parameters and the presence of VLP as possible indicators of proarrhythmic substrate in patients with COPD. We prospectively enrolled 41 consecutive patients in the COPD group and 63 patients witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Yildiz et al [33] reported a signiicantly increased total QRS duration in patients with COPD compared to control subjects and LVPs but no signiicant association with premature ventricular contractions. Despite higher prevalence of LVPs, premature ventricular contractions, and complex ventricular arrhythmias in patients with COPD compared to healthy controls, SAECG had litle value in stratiication of ventricular arrhythmia risk in a study including 41 patients with COPD and 63 patients without any history of pulmonary disease [27]. …”
Section: Follow Up Referencesmentioning
confidence: 88%
See 1 more Smart Citation
“…Yildiz et al [33] reported a signiicantly increased total QRS duration in patients with COPD compared to control subjects and LVPs but no signiicant association with premature ventricular contractions. Despite higher prevalence of LVPs, premature ventricular contractions, and complex ventricular arrhythmias in patients with COPD compared to healthy controls, SAECG had litle value in stratiication of ventricular arrhythmia risk in a study including 41 patients with COPD and 63 patients without any history of pulmonary disease [27]. …”
Section: Follow Up Referencesmentioning
confidence: 88%
“…The association between LVPs and rejection of heart transplant is explained by occurrence of areas of myocardial ibrosis, due to cell changes caused by alloreactive T lymphocytes against graft antigens and ischemia-reperfusion injuries as soon as the blood low is reestablished [22]. 20 young heart transplant patients SAECG is not efective in detecting heart transplant rejection in young patients Horenstein et al [21] Extracardiac disorders were also associated with LVPs, especially hypertension, metabolic syndrome, obesity, eating disorders, diabetes mellitus, renal failure, chronic obstructive pulmonary disease (COPD), acromegaly, thalassemia, connective tissue diseases, epilepsy, and schizophrenia [6,[23][24][25][26][27]. Antiarrhythmic therapy, thrombolytic drugs, statins, steroids, and coronary interventions may inluence LVPs [6].…”
Section: Late Ventricular Potentialsmentioning
confidence: 99%
“…QRS duration > 120 ms, RMS40 > 38 ms and LAS40 < 20 μV were considered abnormal [24]. Presence of two or more abnormal SAECG measurements was considered indicative of VLP [24, 25]. …”
Section: Methodsmentioning
confidence: 99%